Mass surveillance and the militarization of cyberspace in post-coup Thailand - Pinkaew Laungaramsri (2018)
Post-coup Thailand has witnessed a troubling shift toward censorship, surveillance, and suppression in cyberspace. With cyber security ranking prominently on the military's agenda and the expansion of the military's cyber intervention, the country's online infrastructure has undergone politicization, securitization, and militarization. This paper argues that the militarization of cyberspace in Thailand represents the process in which cyber warfare capabilities have been integrated with other military forces and with support from the masses. This process has been effective through at least three significant mechanisms, including mass surveillance, surveillance by the masses, and normalization of surveillance. Social media have been turned into an absolute digital panopticon. Cyber dystopia, created by the 2014 coup and supported by the masses, has served to sustain a 'state of exception' not only within the territorial borders of the state, but also more importantly, within the virtual space of civil society. Cyber surveillance by the military and the masses has continued to jeopardize the already vulnerable Thai democracy.